PROBABILITY OF PRICE REVERSAL AND INTRADAY TRADING ACTIVITY ON TICK SIZE-25 AT INDONESIA STOCK EXCHANGE - Santoso, Perdana Wahyu (Jurnal Manajemen Teknologi, 2011)
In this paper, I examine the probability of price reversal and the relationship with intraday trading activity in market microstructure context, focusing specifically on interrelate with stock's return, trading volume, frequency of transaction, volatility and liquidity on high tick size (IDR25).This research use purposive random sampling to get some observed samples and data online capturing. Trading fraction of tick-by-tick of trading activity is 15 minutes. To determine price reversal probability, I employ multiple logisticregressions in high frequency data. The conclusion of this research finds that stock's return, trading volume (V), frequency of transaction (F) and proxy V/F affect significantly on probability of price reversal on information uncertainty condition. These are substantial findings of intraday trading activity and overreaction concept at Indonesia Stock Exchange.Keywords: probability, reversal, intraday, trading, IDX.Â